Optimally Designed Shell Enclosures with Tuned Absorbers for Minimizing Sound Power - Constans, Eric W.; Belegundu, Ashok D.; Koopmann, Gary H. (Optimization and engineering, 2000)
This paper presents a design methodology for reducing radiated noise from enclosures using multiple optimized tuned absorbers. The methodology starts from the sound power spectrum of the enclosed noise source and ends with optimally sized/located absorbers on a surrounding thin shell enclosure. The design approach combines a finite element method vibration prediction code, a boundary element method sound power prediction code and a combined stochastic/gradient-based optimization algorithm. A design example has been optimized for a thin shell covering a motor/gearbox. The addition of a small amount of weight (130 g or 1.6% of the weight of the shell) produced substantial reductions in radiated sound power (13 dB in the targeted 1/3 octave band centered at 125 Hz). The design has been validated by experiment.[PUBLICATION ABSTRACT]